Prevalence of post-traumatic stress disorder and traumatic exposure among teachers in post-war communities - Edona Berisha Kida; Genta Jahiu; Theodhori Karaj (Discover Mental Health)
Abstract Studies on war zones typically focus on post-traumatic reactions within the general population, often emphasizing specific demographics such as war veterans, younger individuals, or particular clinical groups. Research on post-conflict zones shares similar patterns, with some studies even exploring how trauma may be transmitted to future generations, particularly within refugee families. However, even when conducted in post-war settings, much of this research predominantly examines trauma transmission within family units. Understanding the post-war effects on communities, especially among teachers, requires careful attention and diverse perspectives, as their emotional and psychological states can significantly influence the children they teach, potentially leading to the transmission of trauma to new generations. Given the profound influence teachers have on the development and well-being of children, this study investigates war-related trauma exposure and the prevalence of Post-Traumatic Stress Disorder (PTSD) among Kosovo's primary school teachers. It uses the Harvard Trauma Questionnaire and includes up to 145 teachers from 8 municipalities. Results indicate that 40% of the sample meets the cut-off criteria for Post Traumatic Stress Disorder (PTSD) symptomatology. While the current study focuses on documenting trauma exposure and PTSD among teachers, it serves as a starting point for future research exploring the potential transmission of trauma through community networks, particularly within schools, and the role of teachers impact in inter-generational transmission of trauma.